Comparing and conceptualising reconstructions; The Barcode 6 revisited - Planke, Terje; Rodum, Christian; Steen, Kristina; Falck, Tori; Stålegård, Lars; Fawsitt, Sarah; Vangstad, Hilde (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
When opening a small boat-building workshop at the Norwegian Maritime Museum in Oslo, Norway in 2009, the intention was to foster collaboration between academics and craft experts. Over the years, the workshop has facilitated the building of several reconstructions of archaeological boats. This paper presents a reflective analysis of the methodologies and outcomes involved in reconstructing the 1595 CE Barcode 6 boat, known as the Vaaghals, which was successfully launched in 2011. Both digital and practical methods are evaluated and discussed.